2022
DOI: 10.3390/ani12243550
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Climate-Resilient Forage Species Sustaining Peri-Urban Dairy Cow Production in the Coastal Grasslands of Benin (West Africa)

Abstract: Along the coast of West Africa, grazing ruminants rely on perennial forage species remaining in uncultivated plots, roadsides, and marshlands during the dry season. To assess the quality of these forages, thirteen drought-tolerant plants were harvested at the mature stage, and the samples were evaluated for chemical composition, in vitro fermentation characteristics, and metabolizable energy (ME) content. They are ten drought-tolerant grasses, including: Andropogon virginicus, Brachiaria deflexa, Cenchorus bif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
(88 reference statements)
1
6
0
Order By: Relevance
“…Several factors such as sampling and chemical composition might affect volatile fatty acid production, which affects pH and microorganism development in the rumen. Surprisingly, previous research focused on natural pasture and cultivated grass in the pineapple growing area of West Africa and reported similar results regarding the total VFA [30]. These results might encourage further research to replace limited feedstuffs during the dry season with alternative resources, such as pineapple by-products, to help the farmers to sustain their productivity through the dry season and maintain animal productivity throughout the year.…”
Section: In Vitro Fermentation Characteristics: Comparing By-products...supporting
confidence: 57%
See 2 more Smart Citations
“…Several factors such as sampling and chemical composition might affect volatile fatty acid production, which affects pH and microorganism development in the rumen. Surprisingly, previous research focused on natural pasture and cultivated grass in the pineapple growing area of West Africa and reported similar results regarding the total VFA [30]. These results might encourage further research to replace limited feedstuffs during the dry season with alternative resources, such as pineapple by-products, to help the farmers to sustain their productivity through the dry season and maintain animal productivity throughout the year.…”
Section: In Vitro Fermentation Characteristics: Comparing By-products...supporting
confidence: 57%
“…An in vitro gas production technique (IVGPT) was applied to evaluate the fermentation characteristics of pineapple by-products [30]. Each sample of pineapple by-products was weighed (1.0025 ± 0.0011 g) in four repetitions in 120 mL bottles with 75 mL of medium in anaerobic condition.…”
Section: In Vitro Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the last day of the in vivo tests, a feces sample was taken from each animal, kept in anaerobic conditions at a temperature of 39 °C, immediately transported to the Food analysis laboratory of the Department of Veterinary Medicine and Animal Production, and used for the preparation of the inoculum for the in vitro test, using the GPT [ 29 , 30 ]. To this end, according to Macheboeuf et al [ 31 ], 50 g of feces was mixed with 100 mL of anaerobic buffer at 39 °C, filtered through four layers of gauze, and diluted 1:1 with the buffer, finally obtaining an inoculum for each of the four horses used for each diet.…”
Section: Methodsmentioning
confidence: 99%
“…Climate change increased the frequency of drought, resulting in fodder shortages during the dry season. Koura et al [ 2 ] identified and assessed the nutritional value of thirteen drought-tolerant plants in the coastal grasslands of Benin in West Africa. Most of these forage plants, particularly Poaceae, were poor in nutritional value; however, the cultivation of some promising drought-tolerant plants such as Dactyloctenium aegyptium , Zornia latifolia , and Chamaecrista rotundifolia , which showed the best nutritional characteristics, could be used to sustain ruminant production along these coastal areas.…”
Section: Sustainable Feeds Investigated In This Issuementioning
confidence: 99%